\(8,=-\dfrac{3}{7}+\left(\dfrac{12-3}{4}\right)-\left(\dfrac{9}{4}-\dfrac{10}{7}\right)\\ =-\dfrac{3}{7}+\dfrac{9}{4}-\dfrac{9}{4}+\dfrac{10}{7}\\ =-\dfrac{3}{7}+\dfrac{10}{7}\\ =\dfrac{7}{7}=1\)
\(8.\dfrac{-3}{7}+\left(3-\dfrac{3}{4}\right)-\left(2,25-\dfrac{10}{7}\right)=\dfrac{-24}{7}+\left(\dfrac{12-3}{4}\right)-\left(\dfrac{9}{4}-\dfrac{10}{7}\right)\)
\(=\dfrac{-24}{7}+\dfrac{9}{4}-\dfrac{9}{4}+\dfrac{10}{7}=\left(\dfrac{9}{4}-\dfrac{9}{4}\right)+\left(\dfrac{-24}{7}+\dfrac{10}{7}\right)=0+-2=-2\)
\(8.\dfrac{-3}{7}+\left(3-\dfrac{3}{4}\right)-\left(\dfrac{9}{4}-\dfrac{10}{7}\right)=8.\dfrac{-3}{7}+\left(\dfrac{12}{4}-\dfrac{3}{4}\right)-\left(\dfrac{63}{28}-\dfrac{40}{28}\right)=8.\dfrac{-3}{7}+1-\dfrac{23}{28}=\dfrac{-24}{7}+1-\dfrac{23}{28}=\dfrac{-96}{28}+\dfrac{28}{28}-\dfrac{23}{28}=\dfrac{-91}{28}=\dfrac{-13}{4}\)